Attributes of Long Duration COVID-19 Workers' Compensation Claims. Issue 5 (15th May 2022) - Bernacki, Edward J.; Hunt, Dan L.; Tsourmas, Nicholas F.; Yuspeh, Larry; Lavin, Robert A.; Kalia, Nimisha; Leung, Nina; Willams, Leila; Green-McKenzie, Judith; Tao, Xuguang (Grant)
Abstract : Controlling for industrial category and gender, age was the predominant factor associated with a prolonged disability due to a work-related SARS-CoV-2 infection. Older workers who develop COVID-19 require more vigilance and planning by physicians to help reintegrate these workers back into the workplace. Abstract : Objective: To examine the attributes associated with long duration COVID- 19 workers' compensation (WC) claims. Methods: A study was conducted on 13, 153 COVID-19 WC claims accepted by a workers' compensation insurance carrier between January 1, 2020 and November 30, 2021. Results: 1) Ninety-five percent of accepted WC claims were closed within the study period; 2) five percent of claims had 30 days or longer of lost time accounting for 65% of total paid WC costs; 3) medical costs increased 8-fold once paid days lost crossed the threshold of 60 days or greater; 4) age was the strongest risk factor associated with increased WC costs and prolonged impairment. Conclusion: Age at the time of infection was the major factor associated with prolonged impairment and high costs of COVID-19 related WC claims.